Nanoscopic Roughness Characterization of Chitosan with Buried Graphene Oxide for Fuel Cell Application - Ahmed Kreta; Egon Pavlica; Mojca Božič; Gvido Bratina (Engineering Proceedings, 2022)
The combination of ecologically acceptable polysaccharide (chitosan) and graphene oxide (GO) nanoparticles was used to produce the cell membrane for a direct alkaline ethanol fuel cell (DAEFC). Due to its great power efficiency and minimal influence on the environment, this kind of fuel cell has a lot of potential uses. Recently, the performance of polymer-based DAEFC was significantly improved by the use of graphene. Since the roughness plays an important role in the charge transfer, herein we present our study of the change in the roughness of GO-blended chitosan using different preparation methods and different concentrations of GO.